The Effect Of Financial Literacy, Fintech (Financial Technology) and Intellectual Capital On The Performance Of MSMEs In Depok City, West Java - Nur Hamidah; Rida Prihatni; IGKA Ulupui (Journal of Social Science, 2020)
MSMEs are growing and competing in a business environment that is constantly changing like today in the digital era, it is necessary to monitor and understand company performance to achieve a greater level of business than before, and to determine the extent to which business is being carried out on target. This study aims to analyze and examine the effect of financial literacy, fintech (financial technology), and intellectual capital on the performance of MSMEs in Depok City. Determination of the sample using probability sampling with a proportional random sampling technique than simple random sampling. The number of samples used was 286 samples. The primary data source was taken by using a survey method with a questionnaire. The research design used descriptive and parametric statistical analysis methods with instrument tests and multiple linear regression analysis. The results of this study are financial literacy, fintech (financial technology) and intellectual capital have a positive and significant effect on the performance of MSMEs in Depok City .